2007
DOI: 10.1074/jbc.m707461200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Platelet-derived Growth Factor Receptor Activation by Afadin through SHP-2

Abstract: Upon binding of platelet-derived growth factor (PDGF), PDGF receptor is autophosphorylated at tyrosine residues in its cytoplasmic region, which induces the activation of diverse intracellular signaling pathways such those involving Ras-ERK, c-Src, and Rap1-Rac. Signaling through activated Ras-ERK promotes cell cycle and cell proliferation. The sequential activation of Rap1 and Rac affects cellular morphology and induces the formation of leading-edge structures, including lamellipodia, peripheral ruffles, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 53 publications
2
44
1
1
Order By: Relevance
“…We demonstrated here that afadin plays a critical role in proangiogenic activities of ECs and in vivo angiogenesis and clarified how afadin regulates endothelial signaling downstream of Rap1. Because we have reported that afadin regulates migration and survival in fibroblasts 13,18,26,31 and cell-cell adhesion in epithelial cells, 14,32 the critical roles of afadin in migration, survival and cell-cell adhesion in ECs are consistent with our previous reports. However, the role of afadin in tubulogenesis has not been investigated.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…We demonstrated here that afadin plays a critical role in proangiogenic activities of ECs and in vivo angiogenesis and clarified how afadin regulates endothelial signaling downstream of Rap1. Because we have reported that afadin regulates migration and survival in fibroblasts 13,18,26,31 and cell-cell adhesion in epithelial cells, 14,32 the critical roles of afadin in migration, survival and cell-cell adhesion in ECs are consistent with our previous reports. However, the role of afadin in tubulogenesis has not been investigated.…”
Section: Discussionsupporting
confidence: 80%
“…16, 17 We have demonstrated that afadin regulates cell adhesion and polarity in epithelial cells and neurons, and cell movement of fibroblasts. 14,18,19 The roles of afadin in tubulogenesis and angiogenesis are unknown, but the current literature implies afadin may be a promising candidate protein linking Rap1 to angiogenesis. In this study, we therefore attempt to clarify the roles of Rap1 and afadin in the VEGF-and sphingosine 1-phosphate (S1P)-induced angiogenesis.…”
mentioning
confidence: 99%
“…Activating mutations in SHP2 underlie the Noonan syndrome that manifests as congenital heart disease, short stature, and facial dysmorphia (15,16). SHP2 regulates activated tyrosine kinase receptors including PDGFR, by binding to and dephosphorylating them (17,18). In mice targeted deletions of SHP2 in alveolar epithelial cells (AECs) (19) or macrophages (20) increase predisposition to fibrosis, but the expression of SHP2 in human pulmonary fibrosis or its potential therapeutic usefulness are still unknown.…”
mentioning
confidence: 99%
“…Existing data suggest that these effects are mediated by PDGFR␤, but not PDGFR␣, signaling as the latter cannot be activated by PDGF-BB (7). PDGF binding to PDGFR␤ leads to receptor dimerization, autophosphorylation, and recruitment of Src homology 2 (SH2) domain-containing signaling molecules (16). This in turn leads to MAPK (ERK1/2, p38 MAPK, and stress-activated protein kinase/c-Jun N-terminal kinase) activation (17).…”
Section: Discussionmentioning
confidence: 99%